The effect of the knowledge management processes capability on innovation activities in the Mexican industry - José Guadalupe Flores López; Carlos Armando Jacobo Hernández; Beatriz Alicia Leyva Osuna; Luis Alberto Limón Valencia (Administrative Sciences, 2023)
Mexican industrial organizations focus their efforts on the development of new products and processes, including breakthrough technology. Few studies have focused on the analysis of this corporate effort. After an in-depth theoretical review, it has been detected that most of the research has been based on the study of knowledge management along its dimensions, and there has been no research that incorporates the capabilities of the knowledge management process and its effect on two activities that generate innovation. With the application of a Likert scale-type instrument to 279 industrial companies in Mexico, it was detected that there is a relationship and influence between the dimensions of knowledge acquisition (KAC), knowledge updating (KUP), knowledge protection (KP), knowledge conversion (KC) and knowledge application (KAP) in innovation-generating activities, such as research and development (R&D) and technology acquisition (TA). This was analyzed by the partial least squares (PLS) structural equation technique. Finally, it is important to highlight the contribution that the results of the study have in possible future research that can be carried out, for example, the analysis of the protection of knowledge and its impact on the industry of other countries.
Keywords: 350; capabilities; industry; innovation; knowledge